Are Patients Presenting with an Achilles Tendon Rupture at Greater Risk of Rupturing Their Contralateral Tendon? A Retrospective Cohort Study with Minimum 2 Years Follow-up. Issue 3 (14th September 2018) - Palma, Joaquin; Villa, Andres; Freundlich, Alejandro; Martinez, Jose Dominguez; Secul, Felipe Fuentealba; Carcuro, Giovanni; Nussbaum, Jorge Filippi
Category: Sports Introduction/Purpose: Study Design: Case-control Objective: To determine whether patients presenting with an Achilles tendon rupture are at greater risk of rupturing their contralateral tendon when compared to general population. Summary of Background Data: Extrinsic risk factors for Achilles tendon rupture, such as fluoroquinolones or local injections with corticosteroids, are well recognized. Genetic predisposition is another factor that has been proposed, since this pathology is more frequently seen in certain populations. Thus, it can be theorized that patients who have presented an Achilles tendon rupture are at higher risk of rupturing their contralateral tendon compared to general population. Previous reports by Arøen et al suggest than 10 out of 154 patients presented a contralateral injury (OR:176). Methods: Data from patients operated on from an acute Achilles tendon rupture were retrospectively retrieved from two academic centers. Patients were included if they had at least 2 years since their surgery and were willing to participate in the study. Each patient answered a telephone questionnaire regarding prior symptoms, contralateral rupture and risk factors (flouroquinolones, local corticosteroids and tobacco). Patients were excluded if they did not answer all questions or were unable to be contacted. Since data in our population is lacking, we used the overall incidence of Achilles tendon rupture published by Sheth et al. as the expected rate of Achilles tendon rupture in the general population. This value was compared to our cohort's contralateral injury incidence to obtain an effect measure (odds ratio). Results: 246 consecutive Achilles tendon ruptures were treated during a 6-year follow-up period (2008-2016). 25 patients (8.5%) ruptured their contralateral tendon, equivalent to an incidence of 1407 ruptures per 100.000 inhabitants per year. Reported incidence of Achilles tendon rupture in the general population is 29 per 100.000 inhabitants per year. Odds ratio compared to the general population was 49.2 (95% CI: 34.1 – 73.7) (p <0.0001). Median time to contralateral rupture was 21.6 months (12 – 55) after the initial injury. There were no significant differences regarding age, sex, presence of external risk factors or prior symptoms in the group with a contralateral rupture. 81 patients (33%) experienced tendon pain of at least two weeks duration in relation to their initial rupture. Conclusion: Conclusion: Patients who sustain an Achilles tendon rupture are at higher risk (OR 49.2) of rupturing their contralateral tendon when compared to the general population. In our group, median time for the contralateral injury was 21.6 months. Discussion: Preventive strategies should be directed and conducted in this high risk population. Orthopedic surgeons should consider this information when counseling patients who sustained an Achilles tendon rupture.